(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract Therapy and pathophysiology are foundational subjects in nursing education, equipping students with the knowledge to understand disease mechanisms and therapeutic interventions. This article explores the importance of teaching these disciplines to nursing students and provides strategies for effective instruction in these critical areas.